OCD in animal models using quinpirole as dopaminergic inductor of perseverative behaviour - C. Campos-García Rojas; F. Jiménez-Ponce; A. Flores-Vargas; A.P. García (Revista Médica del Hospital General de México, 2015)
In the reviewed articles, quinpirole is used as a dopamine D2 and D3 receptor agonist to induce persistent behaviour in animal models. Dopamine has been related to perseverative behaviour. The perseverative behaviour was observed in an open field with objects of different shapes and sizes. The main structures studied with this methodology are the orbitofrontal cortex, striatum, thalamus, basolateral amygdala and nucleus accumbens. The animal models studied comply with the face, predictive and construct validity.